Motivations for adolescent self-harm and the implications for mental health nurses - DOYLE, LOUISE; Sheridan, Ann; Treacy, M.P. (My University, 2017)
Introduction:Although self-harm is a relatively common occurrence in adolescents, there is a lack of understanding about the motivations behind it. A poor understanding of self-harm contributes to negative perceptions about those who self-harm and a poor healthcare experience. Aim & Methods: This study identifies motivations behind self-harm in school-based adolescents using a cross-sectional survey. Motivations behind self-harm were elicited using a scale and open-ended responses. Results: Of the 856 adolescents who completed the survey across 11 post-primary schools, 103 reported a history of self-harm. The most commonly endorsed reason for self-harm was to ‘get relief from a terrible state of mind’ (79%). Open-ended responses were consistent with scale responses with most reporting that they self-harmed to relieve distressing emotions. Discussion: Findings provide support for the affect-regulation model of self-harm with support also demonstrated for the self-punishment and anti-dissociation models. There was little support for the interpersonal-influence model suggesting that the commonly held belief that self-harm is attention-seeking is one attributed by others to young people, and not widely reported by young people themselves.Implications for practice: Mental health services need to be responsive to the needs of young people who self-harm which requires eliciting and understanding the individual and multiple meanings behind self-harm to best inform treatment options.
PUBLISHED
Keywords: Adolescents; Attitudes; Mental health nurses; Motivations; Self-harm; Understanding; Adolescent Self-Harm